Covid-19 and Neuro-Behavioral Economics: A Conceptual Framework to Improve Physical and Mental Health among Remote Workers - Deepa Dongarwar, MS; Korede K. Yusuf, MBBS, PhD; Sitratullah O. Maiyegun, MD, MRCP (UK); Sahra Ibrahimi, MPH; Chioma Ikedionwu, MD; Hamisu M. Salihu, MD, PhD (Global Health and Education Projects, Inc., 2020)
Long-term home confinement during the ongoing COVID-19 can have negative mental and physical health consequences, which in turn can reduce productivity among those working remotely. We sought to delineate factors related to neuro-behavioral economics that employers should consider for their employees who are teleworking during the current Covid-19 pandemic. Physical and mental well-being are intertwined and are strongly correlated to high productivity at workplace. By integrating the factors of neuro-behavioral economics into the work culture, companies will alleviate work-related stress leading to improved mental and physical functioning; thus leading to increased productivity. Key words: • Neuro-behavioral economics • COVID-19 • Teleworking • Mental health   Copyright © 2020 Dongarwar et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.